An immersive and interactive visualization system by integrating distinct platforms - Neto, Mario Popolin; Eler, Danilo Medeiros [UNESP]; Moraes, Alessandro Campanha De [UNESP]; Brega, Jose Remo Ferreira [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
Visualization applications can be performed on distinct platforms, such as mobile devices and multi-projection systems. Each platform offers specific features to provide further data understanding, and a system that integrates these platforms in a complementary manner is a real challenge. In this paper, we present an immersive and interactive visualization system that aims to explore data from relational databases using 3D graphs representations, where multiple simultaneous users can visualize and interact with the data through a multi-projection system and mobile devices. A single visualization application was created for both platforms using the Unity game engine, and an Unity external package for Virtual Reality applications development, that supports multi-projection system over a PC cluster and passive stereoscopy. Our visualization system aims to provide the users a better data understanding using a 3-screens multi-projection system as data overview, and mobile devices as display and interaction device for navigation and additional information visualization. We also introduce an user case, where the visualization system is used in order to support developers regarding structural problems in a large relational database.
Keywords: Information visualization; Mobile devices; Multi-projection system; PC cluster; Unity game engine; Virtual reality